A consensus guide to preclinical indirect calorimetry experiments - Banks, Alexander S; Allison, David B; Alquier, Thierry; Ansarullah; Austad, Steven N; Auwerx, Johan; Ayala, Julio E; Baur, Joseph A; Carobbio, Stefania; Churchill, Gary A; Dall, Morten; de Cabo, Rafael; et al. (Nature metabolism, 2025)
Understanding the complex factors influencing mammalian metabolism and body weight homeostasis is a long-standing challenge requiring knowledge of energy intake, absorption and expenditure. Using measurements of respiratory gas exchange, indirect calorimetry can provide non-invasive estimates of whole-body energy expenditure. However, inconsistent measurement units and flawed data normalization methods have slowed progress in this field. This guide aims to establish consensus standards to unify indirect calorimetry experiments and their analysis for more consistent, meaningful and reproducible results. By establishing community-driven standards, we hope to facilitate data comparison across research datasets. This advance will allow the creation of an in-depth, machine-readable data repository built on shared standards. This overdue initiative stands to markedly improve the accuracy and depth of efforts to interrogate mammalian metabolism. Data sharing according to established best practices will also accelerate the translation of basic findings into clinical applications for metabolic diseases afflicting global populations.
Keywords: Animals; nepřímá kalorimetrie; Humans; zvířata; lidé; Energy Metabolism; energetický metabolismus; Calorimetry, Indirect